Land surrounded by water with numerous boats both landed and in the water, Northwest Territories. Note on the front reads: ""Entrance to Hay River from Great Slave Lake"". (Thomas A. Edge Archives & Special Collections, 1899)
photograph : b&w 12. 5 x 8 cm